Global Outcome in Patients with Left Ventricular Assist Devices - Fendler, Timothy J (Am J Cardiol, 2017)
LVADs improve survival and quality of life (QOL) for most, but not all, patients with advanced heart failure. We described a broader definition of poor outcomes post-LVAD, using a novel composite of death, QOL, and other major adverse events. We evaluated the frequency of poor global outcome at 1 year post-LVAD among 164 patients (86% INTERMACS Profile 1-2; shock or declining despite inotropes) at a high-volume center. Poor global outcome (comprising death, poor QOL [KCCQ <45], recurrent heart failure [≥2 heart failure readmissions], or severe stroke) occurred in 58 (35%) patients: 37 died, 17 had poor QOL, 3 had recurrent heart failure, and 1 had a severe stroke. Patients with poor global outcomes were more likely designated for destination therapy (46% vs. 24%, p=0.01), spent more days hospitalized per month alive (median [IQR], 18.6[5.0-31.0] vs. 3.7[1.8-8.3], p<0.001), and had higher intracranial (12% vs. 2%, p=0.031) and gastrointestinal (44% vs. 28%, p=0.056) hemorrhage rates over the year post-implant. While LVADs often improve survival and QOL, ~1/3 of high acuity patients experienced a poor global outcome over the year post-LVAD. In conclusion, composite outcomes may better capture events that matter to patients with LVADs and thus support informed decisions about pursuing LVAD therapy.